2018
DOI: 10.1002/aelm.201800090
|View full text |Cite
|
Sign up to set email alerts
|

A Universal Platform for Fabricating Organic Electrochemical Devices

Abstract: cost-effectively processed at room temperature, and to volumetrically uptake large amounts of electrolytes, OEDs have recently garnered much interest for applications in bioelectronics. [1][2][3] These include biosensing, energy storage, neural recording, and stimulation, [4,5] drug delivery, [6] and electroceuticals [7] to name a few. Out of the many available architectures, a device of choice that has been heavily investigated in recent years is the organic electrochemical transistor (OECT). In a typical OEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
63
0
9

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 42 publications
(97 reference statements)
5
63
0
9
Order By: Relevance
“…As a result, the position of the gate dielectrics was normally restricted to the top side of devices (i.e., FETs in a top‐gate structure) in order to enhance the charge injection from metal electrodes to the accumulation layer formed on the top surface of the polymer . Recently, the combination of poly(2,5‐bis(3‐tetradecylthiophen‐2‐yl)thieno[3,2‐b]thiophene) (PBTTT) and 2,3,5,6‐tetrafluoro‐7,7,8,8‐tetracyanoquinodimethane (F 4 ‐TCNQ) as host and dopant material, respectively, has produced a highly conducting polymer that has been studied as a candidate for a synthetic metal and high power‐factor thermoelectric material . Interestingly, this combination achieved an efficient bulk‐doping of PBTTT by solid‐state diffusion which implied that the F 4 ‐TCNQ dopant molecules diffused into the PBTTT film all the way down to the interface between the PBTTT film and the SiO 2 /Si substrate .…”
mentioning
confidence: 99%
“…As a result, the position of the gate dielectrics was normally restricted to the top side of devices (i.e., FETs in a top‐gate structure) in order to enhance the charge injection from metal electrodes to the accumulation layer formed on the top surface of the polymer . Recently, the combination of poly(2,5‐bis(3‐tetradecylthiophen‐2‐yl)thieno[3,2‐b]thiophene) (PBTTT) and 2,3,5,6‐tetrafluoro‐7,7,8,8‐tetracyanoquinodimethane (F 4 ‐TCNQ) as host and dopant material, respectively, has produced a highly conducting polymer that has been studied as a candidate for a synthetic metal and high power‐factor thermoelectric material . Interestingly, this combination achieved an efficient bulk‐doping of PBTTT by solid‐state diffusion which implied that the F 4 ‐TCNQ dopant molecules diffused into the PBTTT film all the way down to the interface between the PBTTT film and the SiO 2 /Si substrate .…”
mentioning
confidence: 99%
“…Indeed, surface plasmon resonance studies using chips functionalized with either lipid MLs or bilayers have found little difference in terms of binding of antimicrobial compounds, indicating that for the initial interactions, the inner leaflet of the membrane is not essential . We chose to use poly(3‐hexylthiophene‐2,5‐diyl) (P3HT) as the active material of our lipid ML‐integrated transducer, following studies showing P3HT allows ion penetration upon swelling in an organic solvent, enabling the so‐called OECT mode of operation. The electrolyte solution was made by dissolving an anhydrous tetrabutylammonium hexafluorophosphate (TBA‐PF 6 ) ion pair in dichloromethane (DCM), found to have optimal characteristics in terms of solubility, as well as ion exchange properties between the polymer and the electrolyte.…”
mentioning
confidence: 99%
“…Faria and coworkers recently showed how several hydrophobic polymers, taken directly from the organic electronics community without laborious side-chain modifications, could display mixed conduction when interfaced with a non-aqueous liquid. 139 Work by Ginger and co-workers have likewise helped shed light on ion conduction in archetypical P3HT-based OECTs, which is highly dependent on the size of the ions and their hydration shells. 197 Such multi-faceted approaches and inter-disciplinary collaborations across (bio)chemistry, physics and engineering are crucial for rapid development of new materials, device architectures and sensing platforms.…”
Section: Discussionmentioning
confidence: 99%
“…20 A 2018 work by Pitsalidis et al therefore selected P3HT as a suitable material for an OECT, 37 their reasoning citing its known ability to facilitate ion penetration by swelling in organic solvents. 139,140 Their P3HTbased OECT was able to measure modelled bacterial membrane disruption by application of antibiotics. The device featured a top-gate electrode exposed to an aqueous phase, with a dichloromethane phase below containing the electrolyte tetrabutylammonium hexafluorophosphate (TBA-PF6) in contact with the semiconducting material.…”
Section: Poly(3-hexylthiophene) (P3ht)mentioning
confidence: 99%